Financial distress and its determinants: Evidence from insurance companies in Ethiopia - Yonas Nigussie Isayas (Cogent Business & Management, 2021)
This research is aimed to investigate the determinants of financial distress of insurance companies in Ethiopia using balanced panel data from eleven insurance companies for the period covering from 2008 to 2019. A quantitative approach and explanatory design were employed to realize the stated objectives. To achieve the study objectives, secondary data were collected from annual financial statements of sampled insurance companies for the stated period and analyzed using descriptive statistics and a random effect (RE) regression model. The descriptive statistics output of the study revealed that sampled insurance companies are in the safe zone. The RE regression model results show that profitability, firm size, leverage, and company age were negatively correlated to financial distress having a strong negative effect on financial distress. On the other hand, asset tangibility and loss ratio have a positive and statistically significant effect on insurance companies' financial distress. Based on the analysis of findings, the study suggests that Insurance Companies in Ethiopia shall be more concerned about the internal environment (factors) while developing policies and strategies to manage the financial distress condition.
Keywords: 650; altman’ s z-score; determinant factors; ethiopia; financial distress; insurance companies